Auto Dissemination Effect from Female German Cockroach Exposed by Metarhizium anisopliae and Beauveria bassiana to Male German Cockroach - Sanjaya, Yayan; Saefudin, Saefudin; Kusnadi, Kusnadi; Suhara, Suhara (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2024)
Cockroach control should be based on Integrated Vector Pest Management connected to healthy food. This research investigated the auto dissemination phenomenon from infected females to males by the mating process. The method used is a randomized design experiment with 4 treatments and 5 replications. The result showed that the auto dissemination effect occurred from infected females to males during the mating process. The highest concentration caused a higher effect while M. anisopliae has a potential effect to control effective and safe cockroaches.